EDUCAÇÃO CIENTÍFICA NA INFÂNCIA: FORMAÇÃO DE PEDAGOGOS POR MEIO DO ENSINO COLABORATIVO - Bisognin, Thayane (2021)
The current work presents a study conducted in a private education institution of Santa Maria together with the Post Graduate Program in Science and Mathematics Education of the Franciscan University aiming at Teacher Education as line of research. This paper defends that the collaborative learning may be constituted as a teaching formative proposal in order to promote the Scientific Education. To do so, it had, as an objective, to investigate the potential of collaborative teaching as a formative teaching proposal aimed at the promotion of Science Education in childhood. The theoretical and methodological approach was based on qualitative research, grounded on the research training. The participants of this research were three pedagogues who work in early years' classes and voluntarily accepted to participate in the study. For data collection, the following instruments were used: oral diagnostic interview, field diary, through the researcher's observations, and final questionnaire. To answer the proposed objective, the continuing education was carried out in three stages. In the first stage, an oral narrative interview was conducted through the Meet platform. In this stage, the purpose was to identify the pedagogues' conceptions about Science Education and to observe the Science contents, in the early years, to be taught through collaborative teaching. In the second stage, the purpose was to plan and develop, collaboratively, activities that could promote Science Education for the Early Years. This was done through meetings, also remotely, in which the researcher and the study participants had the opportunity to form each other and to form each other collaboratively. In the third stage, a questionnaire was applied at the end of the training, aiming to analyze the perceptions of the participant group about the experience of collaborative teaching in the promotion of Science Education. For data analysis, Content Analysis was employed and, through the treatment and analysis of the data, it was possible to identify the pedagogues' perceptions about Science Education, the challenges in collaborative training, training in times of pandemic, and the potential of collaborative groups. It is concluded that the training through the collaborative group enabled moments of reflection among the participants, moments of debate and acquisition of knowledge, as well as encouraged the teachers to new experiences, motivating them to seek methodologies and activities that promote Science Education in their classes.